Teacher Learning Management: A Key to Improving Student Academic Outcomes - Samsudding, Andi; Thaha, Hisban; Hasbi, Hasbi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study aimed to provide an overview of the implementation of teacher learning management in improving student academic achievement at Madrasah Tsanawiyah Darussalam Buriko. Data were collected through interviews, observations, and documentation using a qualitative descriptive method. The findings indicate that effective learning management at Madrasah Tsanawiyah Darussalam Buriko involves three key stages: (1) Learning Planning: Lesson plans and other administrative tools are prepared, although often only to meet administrative requirements. (2) Implementation: Teachers generally follow their lesson plans, except in certain subjects where they rely solely on student textbooks. (3) Evaluation: This involves formative and summative assessments and evaluations of students' spiritual and social attitudes. Improved student learning outcomes are evidenced by fewer remedial cases attributed to teachers' innovative methods. However, challenges include insufficient infrastructure, additional teacher assignments, inadequate knowledge of planning and implementation, limited study duration, and student-related issues such as afternoon drowsiness, lack of enthusiasm, and discipline problems.This study aimed to provide an overview of the implementation of teacher learning management in improving student academic achievement at Madrasah Tsanawiyah Darussalam Buriko. Data were collected through interviews, observations, and documentation using a qualitative descriptive method. The findings indicate that effective learning management at Madrasah Tsanawiyah Darussalam Buriko involves three key stages: (1) Learning Planning: Lesson plans and other administrative tools are prepared, although often only to meet administrative requirements. (2) Implementation: Teachers generally follow their lesson plans, except in certain subjects where they rely solely on student textbooks. (3) Evaluation: This involves formative and summative assessments and evaluations of students' spiritual and social attitudes. Improved student learning outcomes are evidenced by fewer remedial cases attributed to teachers' innovative methods. However, challenges include insufficient infrastructure, additional teacher assignments, inadequate knowledge of planning and implementation, limited study duration, and student-related issues such as afternoon drowsiness, lack of enthusiasm, and discipline problems.